Number of spermatogenic cells and testes histology of mice (Mus musculus L.) after treated with different times and intervals of red calliandra (Calliandra calothyrsus Meissn.) leaf extract - Pranadya, Ni Made Estriana; Setyawati, Iriani; Yulihastuti, Dwi Ariani (Jurnal Biologi Udayana, 2019)
Tannin compounds in the form of tanic acid are known to inhibit the acrosine activity of spermatozoa and plasminogen activator, which is an antifertility mechanism. Red Calliandra ( Calliandra calothyrsus Meissn . ) leaves have the potential to be developed as herbal medicines, but these leaves contain high condensed tannins, so research needs to be done to determine the effect of red kaliandra leaf extract on the reproduction of male mice.This research used a completely randomized design (CRD) in a factorial patern with four doses and three replications, i.e. control (NaCl 0,9%), doses of red caliandra leaf extract of 2, 4 and 6 mg/kg body weight and time interval of 7, 14 and 21 days. The testes organ were taken and processed histologically by Paraffin Methods and Hematoxylin-Eosin staining. Parameters observed were the amount of spermatogonia, spermatocyte and spermatid cells of male mice. A directly calculation method was done by observed the cells of tubulus seminiferous histology for each treatment used a microscope camera and Image Raster software (Optilab). The data were analyzed with One Way Anova and Duncan Multiple Range Test (DMRT). C alliandra calothyrsus leaf extract with different doses and time intervals decreased the amount of spermatogonia, spermatocytes and spermatids cells in the testes tubulus seminiferous of male mice, the arrangement of spermatogenic cells are increasingly irregular and the lumen were not full filled with spermatozoa cells.